ANALISIS KINERJA HEAT EXCHANGER PADA PREHEATER CDU V DI KILANG RU V BALIKPAPAN - Ibnu Eka Rahayu; Siti Nur Izzah; Muhammad Rahadian Hidayat (Politeknik Negeri Samarinda, 2021)
Separation of crude oil in a petroleum processing plant requires a tool for heat exchanger. Heat Exchanger is used to transfer heat between two or more fluids that have a temperature difference, ranging from a high-temperature fluid to a low-temperature fluid. This process at PT. PERTAMINA RU V Balikpapan is located in the Crude Distillation Unit V (CDU V). The part of the heat exchanger that serves as preheating of petroleum is E-201-01A / B to E-201-11 or commonly referred as a pre-heater circuit. The important role of the pre-heater in the Crude Distillation Unit (CDU V) is significant in order to evaluate the performance of the heat exchanger so that it can be used as a basis for carrying out the cleaning process if it is found when its performance has decreased. Performance evaluation is conducted by comparing the Dirt Factor / Fouling factor (Rd) of the design data and the actual data obtained. The results obtained were heat exchanger E-201-04A / B, E-201-05A / B, E-201-06, E-201-08A / B, E-201-09, E-201-10A / B, and the E-201-11 had the actual Rd value higher than the design Rd, which indicated that there had been a decrease in performance on the heat exchanger. Heat exchanger E-201-04A / B, E-201-05A / B, E-201-06, E-201-08A / B, E-201-09, E-201-10A / B, E-201- 11 had the actual Rd value lower than the design Rd which indicated that the heat exchanger was still performing well. Heat exchangers that have a higher Actual Rd value than RD design are recommended to carry out immediate cleaning according to the conditions of the tool.